The RALF1–FERONIA Complex Phosphorylates eIF4E1 to Promote Protein Synthesis and Polar Root Hair Growth - Zhu, Sirui (2020)
The molecular links between extracellular signals and the regulation of localized protein synthesis in plant cells are poorly understood. Here, we show that in Arabidopsis thaliana, the extracellular peptide RALF1 and its receptor, the FERONIA receptor kinase, promote root hair (RH) tip growth by modulating protein synthesis. We found that RALF1 promotes FERONIA-mediated phosphorylation of eIF4E1, a eukaryotic translation initiation factor that plays a crucial role in the control of mRNA translation rate. Phosphorylated eIF4E1 increases mRNA affinity and modulates mRNA translation and, thus, protein synthesis. The mRNAs targeted by the RALF1–FERONIA–eIF4E1 module include ROP2 and RSL4, which are important regulators of RH cell polarity and growth. RALF1 and FERONIA are expressed in a polar manner in RHs, which facilitate eIF4E1 polar localization and thus may control local ROP2 translation. Moreover, we demonstrated that high-level accumulation of RSL4 exerts negative-feedback regulation of RALF1 expression by directly binding the RALF1 gene promoter, determining the final RH size. Our study reveals that the link between RALF1–FERONIA signaling and protein synthesis constitutes a novel component regulating cell expansion in these polar growing cells.